Evaluación de la acción del Programa nacional de alimentación escolar Qali Warma en la pandemia de COVID-19 en el distrito de Ate, 2020 - Chávez Villanueva, Julia Idola (2022)
The general objective of this research was to evaluate the action of the Qali Warma National School Feeding Program in the COVID-19 pandemic in the Ate district, 2020. The study was of a mixed approach, of a basic type with a triangulation design (DITRIAC). The selection of the participants was made for convenience, considering several inclusion criteria, and was made up of a group of 2 school feeding committees of the public education institutions of Ate, the interview technique was applied with an interview guide. semi-structured and the technique of the questionnaire having as an instrument the same. The instrument was validated with the binomial test (quantitative type content validity) being less than 0.05 (0.00195). The results showed that through the interview with the experts, conformity is shown for the food products and recommendations for the forms of delivery in each educational institution, in the quantitative results there is a higher percentage and the investigation concludes that the Qali Warma program is a National early childhood public policy instituted to safeguard the comprehensive development of children, being suitable for families that have children of preschool and school age during the pandemic.